2017
DOI: 10.1371/journal.pone.0169042
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation and Phylogenetic Relationships Are Revealed by ITS1 Secondary Structure Analysis and Single-Nucleotide Polymorphism in Ganoderma lucidum

Abstract: Ganoderma lucidum is a typical polypore fungus used for traditional Chinese medical purposes. The taxonomic delimitation of Ganoderma lucidum is still debated. In this study, we sequenced seven internal transcribed spacer (ITS) sequences of Ganoderma lucidum strains and annotated the ITS1 and ITS2 regions. Phylogenetic analysis of ITS1 differentiated the strains into three geographic groups. Groups 1–3 were originated from Europe, tropical Asia, and eastern Asia, respectively. While ITS2 could only differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…Intra-strain heterogeneity in the ITS sequences has been reported for species such as G. applanatum var. gibbosum , G. fornicatum , G. japonicum , G. lucidum and G. neojaponicum [45,46]. Sequence variation within strains varies and may occur within ITS1, ITS2 or the 5.8S region.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-strain heterogeneity in the ITS sequences has been reported for species such as G. applanatum var. gibbosum , G. fornicatum , G. japonicum , G. lucidum and G. neojaponicum [45,46]. Sequence variation within strains varies and may occur within ITS1, ITS2 or the 5.8S region.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cho et al [ 41 ] reported a lower β -glucan content (<20 g/100 g dm) for G. lucidum specimens originating from Korea, Japan, Taiwan, USA and Brazil. Considering the taxonomy confusion of G. lucidum , it is possible that these specimens differ from the European G. lucidum [ 30 ]; therefore, differences in β -glucan production could be expected between closely related species. Another possible explanation is the extraction method.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the fungus has been reported worldwide based mainly on morphological characteristics [ 33 , 34 ]. Recently, molecular and taxonomic data have confirmed that Asian ‘ G. lucidum ’ differs from the originally described species from Europe [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies based on morphological characteristics and molecular data have pointed out that 'G. lucidum' from Asia does not correspond with the originally described European species (Moncalvo & Ryvarden 1997;Cao et al 2012;Wang et al 2012;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 95%